Qamar Jodhpuri an Unidentified Poet of the Pakistan Movement - Rashid, Abdul Qudoos Hassan; Shahani, Shafique Ahmed (sourcecoder, 2023)
Qamar Jodhpuri is one of those prominent personalities of Hyderabad Sindh who took an active part in Pakistan movement. He was vigorously involved in settlement of refugees and social work was the member of Basic Democracy (BD) as well as an active participant in literary activities. Moreover, one of the best aspects of his personality was that he was associated with literature and poetry but regrettably he has no noticeable place as a poet like other local poets in the literary history of Hyderabad. After formation of Pakistan he is such a link whose discovery can bridge the gap of the city in literary history.